COGNITIVE AND FUNCTIONAL CHANGES FOUND IN POST-COVID-19 SYNDROME IN ELDERLY PEOPLE: INTEGRATIVE REVIEW - Rodrigues, Ingridy Fátima Alves; Silva, Karla Helena Coelho Vilaça e; Stephanus, Andrea Dias; Carvalho, Luiz Sérgio Fernandes de (Cogitare Enfermagem, 2024)
Objective: To identify the most frequent cognitive and functional changes in elderly people after the acute phase of COVID-19. Method: Integrative literature review with a search for articles in the LILACS, MEDLINE, PubMed, and Scopus databases, between June and July 2024. The selection was conducted independently by two reviewers and validated by a third reviewer. Original primary studies were included that involved participants with a majority or median age over 60 years, with post-COVID-19 cognitive and functional changes. Results: Heterogeneity was observed in the samples, with a wide range of clinical characteristics, the most prevalent being: dyspnea, fatigue, changes in sleep patterns, and cognitive deficit. Conclusion: The results contribute to a better assessment and conduct. They point to the need to create specific care protocols for elderly people with post-COVID-19 syndrome and to develop more appropriate and targeted interventions for the prevention, reduction, or minimization of persistent symptoms.